Revitalisasi Mahasiswa Fakultas Dakwah dan Komunikasi dalam Islamic Civilazation - Richway Richway (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2016)
Abstrak: Faculty of Dakwah and Communication UIN Raden Fatah Palembang constitute a valuable asset in creating propaganda resources to keep the Islamic Civilization. But the conditions of the students of the Faculty of Dakwah now showing symptoms of pragmatism. Most of them just put the value of academic and forget the obligations and responsibilities as a volunteer custodian of Islamic Civilization in the community. Critical thinking skills in addressing any problems in society increasingly minimal. Hence the need for mental revitalization and strategy in delivering propaganda in society. Hone back critical thinking skills and the ability to write expected to answer the social problems caused by various factors. This effort is expected to also not just limited discourse, but no real steps from the Faculty of Dakwah itself to the revitalization of mental and propaganda strategy.